Advocacy Corner: High School Math Pathways---Ohio's Pathway to Equity - Pachnowski, Lynne; Cannelongo, Anna (Ohio Journal of School Mathematics, 2021)
The authors summarize changes underway in Ohio’s high school mathematics curriculum that provide alternatives to high school Algebra II and beyond. The authors share historical background of the current secondary level mathematics curriculum, the rationale for alternative pathways for Ohio’s mathematics students, and the plan for implementing these pathways in Ohio schools.